2023
DOI: 10.3390/jof9050588
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mycorrhiza on C:N:P Stoichiometry in Senesced Leaves

Abstract: Senesced leaves play a vital role in nutrient cycles in the terrestrial ecosystem. The carbon (C), nitrogen (N) and phosphorus (P) stoichiometries in senesced leaves have been reported, which are influenced by biotic and abiotic factors, such as climate variables and plant functional groups. It is well known that mycorrhizal types are one of the most important functional characteristics of plants that affect leaf C:N:P stoichiometry. While green leaves’ traits have been widely reported based on the different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
0
0
0
Order By: Relevance
“…carbon:nitrogen:phosphorus ratio, lignin concentration), which can influence colonization of decomposers and their interactions, also has a profound impact on this process (Graça et al., 2001; Yue et al., 2022). Moreover, a growing number of studies have suggested that mycorrhizal association of plants has a strong link with leaf chemistry (Keller & Phillips, 2019; Wu et al., 2023; Zhang et al., 2019). Plants associated with arbuscular mycorrhizae (AM) are usually associated with lower lignin and cellulose concentrations (Peng et al., 2022), and lower carbon:nitrogen ratios (Taylor et al., 2016) compared with those associated with ectomycorrhizae (EcM), and such traits can influence the rate at which leaf litter decomposes.…”
Section: Introductionmentioning
confidence: 99%
“…carbon:nitrogen:phosphorus ratio, lignin concentration), which can influence colonization of decomposers and their interactions, also has a profound impact on this process (Graça et al., 2001; Yue et al., 2022). Moreover, a growing number of studies have suggested that mycorrhizal association of plants has a strong link with leaf chemistry (Keller & Phillips, 2019; Wu et al., 2023; Zhang et al., 2019). Plants associated with arbuscular mycorrhizae (AM) are usually associated with lower lignin and cellulose concentrations (Peng et al., 2022), and lower carbon:nitrogen ratios (Taylor et al., 2016) compared with those associated with ectomycorrhizae (EcM), and such traits can influence the rate at which leaf litter decomposes.…”
Section: Introductionmentioning
confidence: 99%
“…C:N:P stoichiometry can reflect nutrient restriction in plants, which is a crucial index of nutrient decomposition [5]. Many studies have focused on the response of the leaf C:N:P stoichiometry to environmental changes at regional scales [6,7]; however, little is known about the fine-root C:N:P stoichiometry.…”
Section: Introductionmentioning
confidence: 99%